A framework for developing sustainable e-learning programmes. (2nd January 2017) - Chipere, Ngoni
Abstract: A framework was created at the University of the West Indies to guide the development of 18 e-learning programmes. The framework is based on three principles for sustainable e-learning design: (1) stakeholder-centredness; (2) cost-effectiveness and (3) high operational efficiency. These principles give rise to nine framework elements: (1) a labour market-driven programming agenda; (2) a continuous improvement quality assurance system; (3) international programme standards; (4) a costing model; (5) course rationalisation; (6) a learning object repository; (7) template-based document preparation; (8) project management and (9) an electronic project work-space. The framework enabled the 18 programmes to be developed on time and on budget. A post implementation staff survey and student course evaluations indicate broad satisfaction with the framework and its implementation. The paper concludes with a reflection on the lessons learned during the development and implementation of the framework.